Retrofit measures in old elementary school buildings towards energy efficiency - Carlos, Jorge S.; Corvacho, Helena (Journal of Civil Engineering and Management, 2010)
A study on thermal retrofit of Portuguese elementary school buildings is presented. The type of school under analysis is one adopted by a large construction campaign that began in the 1940’s. This building stock has a very poor thermal performance and their retrofit was evaluated starting with a case study of a school in the central region of Portugal, where some experimental measures were performed and a calculation method was applied for the heating energy consumption estimation. A solution for the thermal retrofit of the school building external envelope was optimized and the effect on heating energy consumption was evaluated, using ECOTECT, resulting in a reduction of 52% of heating energy needs. The national impact of the thermal retrofit of the whole building stock was characterised in terms of energy savings. Finally, the pre‐heating of the ventilation air was also tested as a complementary measure and its effect evaluated. The solution tested may provide up to 1000 kWh/year of extra heat gains by pre‐heating the ventilation air. It must be underlined though that the performance of these systems is dependent on the thermal properties of their components so higher reductions can be achieved with the improvement of these properties. First Published Online: 10 Feb 2011